STARTEGI MENDULANG EMAS DI GANG KELINCI - JAMALLUDIN JAMALLUDIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This Best Practice aims to improve strategies so that the achievements obtained at MIN Denpasar increase. The targets in this best practice are MIN Denpasar students who get rewards for their achievements in previous schools. Then there are also students who get and achieve achievements in participating in competition events when they are students of MIN Denpasar. In the implementation of this best practice, several strategies were obtained so that the implementation went according to the author's wishes, including the one hundred achievements per year program and the fundraising program. Both programs were successful in producing many achievements that were obtained by MIN Denpasar. With this program, all stakeholders synergize with each other to achieve the target of one hundred championship achievements per year at MIN Denpasar. ABSTRAKBest Practice ini bertujuan unuk meningkatkan strategi agar prestasi yang didapatkan di MIN Denpasar semakin meningkat. Sasaran dalam best practice ini adalah siswa MIN Denpasar yang mendapatkan reward atas prestasi yang sudah diraih di sekolah sebelumnya. Kemudian ada juga siswa yang mendapatkan dan meraih prestasi dalam mengikuti event perlombaan ketika menjadi siswa MIN Denpasar. Dalam pelaksanaan best practice ini didapatkan beberapa strategi agar pelaksanaan berjalan sesuai dengan keinginan penulis diantaranya adalah program seratus prestasi pertahun dan prograng fundraising. Kedua program itu sukses dalam menghasilkan banyak prestasi yang didapatkan oleh MIN Denpasar. Dengan program ini semua stakeholder saling sinergy untuk pencapaian target seratus prestasi kejuaraan pertahun di MIN Denpasar.